2007
DOI: 10.1016/j.jacc.2006.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metabolic Syndrome on Tissue Characteristics of Angiographically Mild to Moderate Coronary Lesions

Abstract: Metabolic syndrome is associated with lipid-rich plaques, contributing to the increasing risk of plaque vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 25 publications
6
53
0
1
Order By: Relevance
“…In that study, there was a significant difference in the ratio of lipid-rich plaque among 3 of the MetS components groups: MetS components 0-2, MetS components 3, and MetS components 4-5. 15 It was concluded that MetS was an independent predictor of lipid-rich plaque, contributing to an increased risk of cardiovascular disease. However, an observational study can not evaluate the impact of MetS and its components on coronary PV change in ACS patients under statin intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, there was a significant difference in the ratio of lipid-rich plaque among 3 of the MetS components groups: MetS components 0-2, MetS components 3, and MetS components 4-5. 15 It was concluded that MetS was an independent predictor of lipid-rich plaque, contributing to an increased risk of cardiovascular disease. However, an observational study can not evaluate the impact of MetS and its components on coronary PV change in ACS patients under statin intervention.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, it is important to note that maximal density of macrophages/mm 2 in atherosclerotic lesions is associated with visceral obesity (30), reduced coronary flow reserve related to body fat distribution and insulin resistance (31), and the MetS associated with lipid-rich plaque (32). In a systematic review and meta-analysis of longitudinal studies (33), it has been reported that individuals with the MetS are at increased risk of a cardiovascular events and death (relative risk 1.78).…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Lipid-rich plaques measured by IB-IVUS proved to be an independent morphologic predictor of nontarget ischemic events after percutaneous coronary intervention, and the risk was particularly increased in patients with elevated serum C-reactive protein levels (Amano et at., 2011). Amano et al reported that patients with metabolic syndrome showed a significant increase in % lipid area (38 ± 19% versus 30 ± 19%, p=0.02) and metabolic syndrome was associated with lipid-rich plaques, contributing to an increase of plaque vulnerability (Amano et al, 2007). Kimura et al demonstrated that the ratio of LDL to HDL cholesterol was an independent predictor of lipid area / non-lipid area .…”
Section: Wwwintechopencommentioning
confidence: 99%